If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(-3+4)-2=-(x-2)
We move all terms to the left:
-3(-3+4)-2-(-(x-2))=0
We add all the numbers together, and all the variables
-(-(x-2))-2-31=0
We add all the numbers together, and all the variables
-(-(x-2))-33=0
We calculate terms in parentheses: -(-(x-2)), so:We get rid of parentheses
-(x-2)
We get rid of parentheses
-x+2
We add all the numbers together, and all the variables
-1x+2
Back to the equation:
-(-1x+2)
1x-2-33=0
We add all the numbers together, and all the variables
x-35=0
We move all terms containing x to the left, all other terms to the right
x=35
| `-6y+10=8` | | 5a+4=32 | | √3x+4+√5x-x=5 | | 19x-22=7x=30 | | 9/14=x/98 | | 287=(x4)+19= | | 24−8x=−16−16 | | √2x-3+10=11 | | 3x+6x+20=96 | | 3x+4x=1-8 | | –8+–3w=–11 | | z=-18-z | | x-0.03x=2100 | | *y+24)/4=4 | | 7y-32=-5(y+4) | | w+4=17 | | 30=2(u-5)-6u | | 7-y/5=3/; | | w−–4=17 | | -10=-1+p | | 10.5-5x=2x | | 3(x−4)^2=18 | | 3(x−4)2=18 | | 2x=105x-8 | | 2^(2x+2)10^(x+1)-10*2^(3x)5^(x)=1200 | | ((x*0,1)+x)=110 | | x*0,1+x=110 | | x*0,1+x=110 | | 14x=12600 | | 14x=12600 | | 3-5x=2x-3 | | --5y+8=7 |